Peningkatan Kompetensi Profesional Guru Melalui Penerapan Pendekatan Supervisi Kolaboratifdi Madrasah Ibtidaiyah Al-Muqorrobin Kecamatan Kandis - Indriyanto, Indriyanto (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
The problem in this research is that not all teachers understand the technique of developing learning materials. This study aims to describe the development of a collaborative supervisionprocess to improve the professional competence of teachers in Madrasah Ibtidaiyah Al-Muqarrobin, Kandis District and increase teacher professional competence in Madrasah Ibtidaiyah Al Muqarrobin, Kandis District after the collaborative supervision approach was applied. Sources of data came from instruments that were submitted to all Madrasah Ibtidaiyah Al-Muqarrobin teachers, Kandis Subdistrict. Data analysis was carried out using descriptive and qualitative analysis, then consulted with the success criteria to find out whether the application ofa collaborative supervisionapproach can improve teacher professionalism at Madrasah Ibtidaiyah Al-Muqarrobin Kandis District. Based on the results of the study, the increase in theprofessional competence of teachers at Madrasah Ibtidaiyah Al-Muqarrobin, Kandis District, was 13.64points. The average professional competence of teachers in the pre-cycle is 56.81 with less criteria and in cycle 1 it is 70.45 with sufficient criteria. The professional competence of teachers also increased from cycle 1 to cycle 2 by 18.19 points. The average professional competence of teachers in cycle 2 is 88.64 with good criteria. Based on the results of the data analysis above, it is concluded that the professional competence of teachers at Madrasah Ibtidaiyah Al-Muqarrobin,Kandis District can be improved through the application of a collaborative supervision approach.